Penyusunan Laporan Keuangan Pondok Pesantren Darussalam Mekar Agung Tahun 2019 Berdasarkan Pedoman Akuntansi Pesantren - Arini Wildaniyati; Miftahul Rifa'i (JAMER : Jurnal Akuntansi Merdeka, 2021)
The Darussalam Mekar Agung Islamic Boarding School is a non-profit organization that is not profit-oriented, but there must be good and correct financial reporting. The main source of income for this Islamic boarding school comes from the contribution of the students. Thus, there must be transparency and accountability in the financial reporting. Islamic boarding schools must be able to produce financial reports in accordance with standards so that these financial reports can be understood by all parties. The purpose of this study is to determine the preparation of financial statements in accordance with the Islamic Boarding School Accounting Guidelines. The research method used is a qualitative method with a descriptive approach. The location of this research is in the Darussalam Mekar Agung Islamic Boarding School, Pucanganom Village, Kebonsari District, Madiun Regency. Data collection obtained by means of observation, interviews, and documentation. The data obtained are primary data and secondary data. Primary data was obtained from Mr. Fahrul Amiruddin as the treasurer of the cottage. And secondary data obtained from the financial reports of Islamic boarding schools. The results of this study indicate that the Darussalam Mekar Agung Islamic Boarding School has not implemented the Islamic Boarding School Accounting Guidelines in financial reporting. The recording is still relatively simple. The treasurer only records income and expenses without making final calculations to adjust income and expenses (debit and credit).